Rational Clinical Use of Blood and Blood products – A summary - Ghartimagar, D (Journal of Pathology of Nepal, 2017)
Blood transfusion is an essential therapeutic intervention. The main role of the blood centre is to provide safe and timely blood and blood component(s) to the patients that will improve the physiological status of the patient. Various blood components can be harvested from a single donation of whole blood. The blood centre ensures that there is an adequate inventory of all blood types and blood components to meet the needs of the patients. The blood centre does donor selection, blood collection, component preparation, screening for transfusion – transmitted infections and blood processing. Serologically compatible blood and components are provided to the patients after meticulous pre-transfusion testing as per the standard protocol. Rational use of blood and blood products means right product is used with the right dose on right time for the right reason.